From North American Free Trade Agreement to United States–Mexico–Canada Agreement (USMCA): US–Mexico Economic Relations in the Context of US National Security (Politeja, 2022)
The article deals with the relationship between the United States and Mexico from the perspective of the US national security. The key areas of strategic interest in Mexico on the part of the United States include: limiting illegal immigration, fighting drug-related crime, economic cooperation, both bilateral and in the wider international dimension, for example the North American Free Trade Agreement. According to the United States, all three factors and their successful implementation are necessary and constituent elements of the national interest of the United States in its most important scope, that is, in increasing the security of the state. The analysis focuses on the U.S. economic relations with Mexico at the turn of the 20th and 21st centuries. The basis of economic relations between these countries is the North American Free Trade Agreement. The genesis of the NAFTA agreement and its effects on mutual relations in the context of the U.S. national interest and security was presented. Additionally, the reasons for President Donald Trump’s change from NAFTA to USMCA are described, from the perspective of U.S. strategic interests.